Climate resilience building in Semi-Arid Lands (SALs): institutional weaknesses and strengths in subnational governments in Brazil - Ferreira Costa, Carlos Germano (Desenvolvimento e Meio Ambiente, 2020)
Well established institutions are an essential factor for the successful realization of sustainable socio-economic and environmental potential in Semi-Arid Lands (SALs). SALs receive limited attention in international climate research and policies; thus, the institutional relationship between governance, policy, and implementation continues to suffer from inconsistencies across governance levels. This research carried out an analysis combining mixed-research methods to collect, record, and analyze data and information regarding institutional and organizational strengths, weaknesses, opportunities, and threats, and local level policy implementation challenges and scope to assess the effectiveness of Disaster Risk Management (DRM) and implementation of adaptation policies at State and local levels in SALs. The inefficiencies observed in the DRM/CCA adaptation processes are concentrated in areas of high governance of state and municipal governments and stem from local communities' reduced organizational and technical capacity. It results in the negligent application of measures and resources to address climate risks. Therefore, this paper contributes to the increasing understanding of the institutional framework's role in the facilitation of local adaptation, revealing what seems to be working well, what is not, how things could improve in Brazilian SALs.